1996
DOI: 10.1063/1.115867
|View full text |Cite
|
Sign up to set email alerts
|

Assembling strained InAs islands on patterned GaAs substrates with chemical beam epitaxy

Abstract: Growth and characterization of midinfrared InGaAs/InAlAs strained triplequantumwell lightemitting diodes grown on latticemismatched GaAs substrates

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
40
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(41 citation statements)
references
References 15 publications
1
40
0
Order By: Relevance
“…Pre-patterned substrates have also been used for ordering of QDs in a more direct way. Miu et al [9] grew by MBE on etched GaAs gratings and found islands to form on the sidewalls of ridges running along [1][2][3][4][5][6][7][8][9][10] direction. Similar results were obtained by Jeppesen et al [10] for Chemical Beam Epitaxy (CBE) deposited InAs islands in wet-etched and partially overgrown trenches and holes on a (100) GaAs surface.…”
Section: Quantum Dots Fabricationmentioning
confidence: 99%
See 1 more Smart Citation
“…Pre-patterned substrates have also been used for ordering of QDs in a more direct way. Miu et al [9] grew by MBE on etched GaAs gratings and found islands to form on the sidewalls of ridges running along [1][2][3][4][5][6][7][8][9][10] direction. Similar results were obtained by Jeppesen et al [10] for Chemical Beam Epitaxy (CBE) deposited InAs islands in wet-etched and partially overgrown trenches and holes on a (100) GaAs surface.…”
Section: Quantum Dots Fabricationmentioning
confidence: 99%
“…In both cases, the projected probability density has elliptical form in the plane (k x , k y ). For the (100) case, the axis of electron wavefunction symmetry is at an angle~30°relative to the main crystallographic direction [1][2][3][4][5][6][7][8][9][10], i.e. it is inclined at around 15°to [100].…”
Section: Effects Of Growth Interruptionmentioning
confidence: 99%
“…The first method uses the directed migration of adatoms to a concave surface area. This can be realized by engineering the surface chemical potential [30,31] using a patterned surface ( figure 7(a)). …”
Section: Control Of Quantum Dot Nucleationmentioning
confidence: 99%
“…Lateral ordering of QDs formed in the Stranski-Krastonov growth mode, otherwise producing randomly arranged QDs, has been achieved by artificial substrate patterning [2][3][4] and combined with vertical strain correlated stacking. 5,6 Artificial patterning techniques, however, often introduce defects and irregularities in the QDs given by the spatial resolution of the lithography and etching steps which degrade the electronic and optical qualities.…”
mentioning
confidence: 99%